Determining the Response Speed of Fire Rescue Vehicles in Arriving at the Emergency Scene - Narzulla o‘g‘li, Doniyorov Azizbek; Elmirzaevich, Javliyev Asomiddin (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2026)
The rapid response of fire and rescue units is one of the most essential parameters in restricting the propagation and reducing the damages generated by fire tragedies in urban settings. On wide paved roads, average travel speed is about 45 km/hr, and is about 25 km/hr on difficult road sections, according to regulatory guidance, and the maximum allowable arrival time for the first unit is commonly 10 minutes. As argued in the literature, particularly in urban settings, large-scale traffic congestion, and specific factors such as the type of vehicle used, time of the day, season of the year, or an administrative decision may disturb the full performance of these standards. This study contributes to bridging the gap between normative knowledge and actual performance of responding decisions using existing operational data of Termez city. This research conducts a statistical modeling and factor analysis of 36 emergency responses recorded between January and December 2022. Average travel speed (Km/h) was computed with distance and travel time, and call flow was modeled empirically and theoretically with a number of approaches, including testing for Poisson distribution with the Pearson criterion. The results indicate the mean fire and rescue arrival speed of 51 km/h in the city of Termez, ranging considerably depending on vehicle type and temporal conditions. The results show that cities cannot expect to suddenly get much faster (to 60 km/h or more) and that increasing the number of depots comes with expensive fixed cost. The study suggests that a purely speed-oriented approach for enhancing the effectiveness of response will likely be ineffective and that attention needs to go to depot placement, operational planning and dispatch management instead.